Effect of NaOH on morphologies and photocatalytic activities of CeO2synthesized by microwave-assisted hydrothermal method - Anukorn Phuruangrat (2018)
© 2017 Elsevier B.V. This research reports the successful synthesis of CeO 2 nanorods as a photocatalyst in a solution containing different content of NaOH by the microwave-assisted hydrothermal method. The phase, morphologies and photocatalytic properties of the as-synthesized CeO 2 samples were characterized by powder X-ray diffraction (XRD), transmission electron microscopy (TEM) and UV–visible spectroscopy. The XRD patterns of products certified that the as-synthesized CeO 2 samples were pure cubic CeO 2 phase. TEM images revealed the presence of as-synthesized uniform CeO 2 nanorods using 20 ml NaOH solution. The influence of NaOH solution on the photocatalytic properties of as-synthesized CeO 2 samples was investigated through degradation of methyl orange (MO) as a model dye. Over 95% photodegradation of MO was degraded by the CeO 2 nanorods within 120 min under UV light irradiation.